Unwanted Short-Term Guests of School: Romani Children’s Access to Education The Case of Mersin, Turkey - Açıkalın, Neriman; Sever, Hasan (Journal of Applied And Theoretical Social Sciences, 2023)
As for all children on earth, education, as a fundamental human right, must be available, accessible, acceptable and adaptable to diverse needs for Romani children as well. This study has addressed the issues of Romani children’s access to education, their reasons for being absent from school, the fact that they are branded as “retarded”, the problems they face when accessing quality education by being based on the data of a field research. According to the data it has been concluded that Romani children in the educational institutions have remained as unwanted short-term guests of the educational institutions, under conditions extremely remote from the principles of inclusive education. This study, which is based on a field research, was conducted in the city of Mersin in Turkey. The process of data collection of this study was realized in two stages. First of all, data were collected through a semi-structured questionnaire form, which sampled 530 Romani households and contained subcategories such as the demographic qualities, employment areas, educational status, exposure to discrimination, daily life practices, etc. of the residents. Beside this quantitative data collecting technique, data were also collected through in-depth interviews on these subcategories and focus group techniques. The heading on which this study will focus will be the educational problems of Romani children in different subcategories of the field research.